Determining the background for implementation of sports-oriented teaching techniques in training of children age of 5–6 years old under the conditions of a preschool educational establishment - Петренко, Геннадій Валентинович (Slobozhanskyi Herald of Science and Sport, 2016)
Petrenko G. Purpose: to identify and substantiate the necessity of the implementation of physical training elements and sports games in education of late preschools. Material & Methods: the analysis of scientific-academic literature and regulatory documents, polling, survey, pedagogical observation, test execution. Results: the attitude toward sports-oriented physical training is based on the analysis of children’s attitude to their sporting activities as well as of their parents and of personnel at pre-school institutions. This article provides the results of children’s motor skills assessment and reveals the necessity of implementation of sports-oriented physical training to the educational experience at pre-school educational institutions. pedagogical observation, test execution. Conclusions: a poor physical health leads to the implementation of physical training technologies and sports games in teaching process at pre-school institutions as an alternative to traditional physical training techniques is the most effective way to motivate preschools to exercise which has a great impact on children’s health and well-being